The economic implications of the beef pricing policy in Zimbabwe - Rodríguez, G. (International Livestock Centre for Africa, 1985)
Analyzes the price structure confronting beef producers and consumers in Zimbabwe as a result of government interventions, and estimates the quantitative response of consumers & producers to changes in beef prices by describing the production structure of the beef sector, trends in beef consumption and demand, producers price structure, supply response parameters and the beef grading scheme.